Motivation as Moderating Variable on the Effect of Moral Reasoning and Ethical Sensitivity Toward the Ethical Behavior of Accounting Students - Hermawan, Sigit; Sari, Lilin Nur Indah (Universitas Negeri Malang, 2018)
This research aims to prove the effect of moral reasoning andethical sensitivity on accounting students’ ethical behavior on the basis of motivation as moderating variables. Respondents on this research were accounting students of Universitas Muhammadiyah Sidoarjo. The data was collected by using questionnaire method.131 questionnaires were distributed and analyzed.This research used multiple linear regression analysis and moderated regression analysis (MRA). On other side, this research was helped by SPSS (Statistical Package for Social Scienci) versi 18.0 software.The result of this research showed that Moral Reasoning and Ethical Sensitivity affects partially to the ethical behavior of accounting students. Meanwhile, motivation was able to moderate the effect of Moral Reasoning and Ethical Sensitivity to the ethical behavior of accounting students.